Analisis Lembaga Yudikatif Dalam Etika Politik Islam Menurut Imam Al-Ghazali - S, Sarmila; Patongai, Alni Avasyah R.A; Mansyur, Nur Islamiah; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses Imam Al-Ghazali's views on the judiciary and Islamic political ethics. This research aims to explain Al-Ghazali's political thoughts which explain the judiciary in Islam and also explain the concept of justice as applied to life. Al-Ghazali emphasized the need for judges who are well trained, have in-depth knowledge of Islamic law, and high moral integrity. This research highlights the importance of transparency in the judicial process to ensure fairness in decisions and strengthen the legitimacy of judicial institutions in the eyes of the public. The independence of the judiciary from political or other external influences is also considered crucial to ensure decisions are based on the law and principles of justice. Al-Ghazali's views provide a valuable framework for understanding how the justice system can be built and strengthened in the context of a just and civilized society. The research method used is a qualitative method by conducting a literature study from one source. Then the data collected will be studied and analyzed to be analyzed carefully in order to get answers to the problems being studied.